Breast Self-Examination: Knowledge, Practice, and Beliefs Among Females in Jordan. (October 2022) - Ahmad, Suhad; Alloubani, Aladeen; Abu-Sa'da, Ruba; Qutaiba, Yasar
Introduction: Worldwide, breast cancer is one of the most common types of cancer. It is the leading cause of cancer-related deaths among females in Jordan. Objective(s): The current study aimed to evaluate breast cancer knowledge levels and practice and assess health beliefs regarding the model supporting self-breast examination (BSE) in a group of females aged between 20 and 60 in Jordan. Methods: Descriptive, cross-sectional, correlational design was used; Two hundred females participated in the study, employing convenient sampling. The adjusted version of the Champion's Health Belief Model Scale (CHBMS) was utilized to collect the data. Results: Most participants were married (F = 128, 64%), and the mean of the participants' age was (36.18, SD = 10.87). About 73 participants (36.5%) don't practice BSE; however, 53 participants (26.5%) plan to practice BSE in the future monthly. The logistic regression model showed that the impact of confidence as positive predictive value on practicing BSE in the last year ( B = 0.141, p < .001) and this year ( B = 0.130, p < .001) was statistically significant. Conclusion: Implications for practice include identifying culturally specific barriers and improving health education programs to trigger breast self-examination utilization.